2014
DOI: 10.30970/sbi.0802.357
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the cytotoxic properties of isatin-containing derivatives of 4-thiazolidinone with different structure toward human tumor cells in vitro

Abstract: Сполуки на основі 4-тіазолідинону та його ізатинвмісні похідні мають широкий спектр біологічних активностей і є потенційними антинеопластичними чинниками. Ми з'ясували, що поєднання 4-тіазолідинонів та ізатину (1Н-індол-2,3-діон) у скла-ді однієї молекули посилює цитотоксичну дію новосинтезованих сполук на лейкоз-ні й карциномні клітини in vitro. Рівень цитотоксичної дії речовин ID-3833, ID-4522, ID-4523, ID-4524, ID-4525, ID-4526, ID-4527 суттєво залежить від наявності атома галогену в 5-му положенні індоліно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Within 20 days of the experiment, we did not observe changes in the appearance, skin condition, behavior, appetite and body weight of the experimental rats of [3][4][5][6][7][8][9] th groups compared to the control group. Only in the second group of animals treated with doxorubicin, a significant reduction in body weight, changes in skin, general weakness and low activity were noticed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within 20 days of the experiment, we did not observe changes in the appearance, skin condition, behavior, appetite and body weight of the experimental rats of [3][4][5][6][7][8][9] th groups compared to the control group. Only in the second group of animals treated with doxorubicin, a significant reduction in body weight, changes in skin, general weakness and low activity were noticed.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of our previous studies [8,9], this compound was characterized by the most pronounced cytotoxic effect and possessed the highest toxic effect in rats compared to the effect of other 4-thiazolidinone derivatives. As expected, the drug 3833 demonstrated the highest nephrotoxicity among the 4-thiazolidinone derivatives used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds of this class are known for their anticancer activity as well as for their other biological effects, such as antibacterial, fungicidal, antiviral, anti-inflammatory, and antidiabetic actions [10]. The results of our previous studies on antitumor efficiency of 4-thiazolidinone derivatives, including those of pyrazoline substitution [9,10] allowed drawing a conclusion that the pyrazoline-thiazolidinone-indoline conjugates demonstrate the most promising results, and that the most active ones are the compounds 3288, 3833 and 3882 [11,12]. The molar masses of these synthetic substances are 559.44 g/ mol (3288), 530.61 g/mol (3882), and 609.51 g/mol (3833).…”
mentioning
confidence: 99%
“…In previous studies, we have demonstrated that combining of thiazolidinone, pyrazoline and 2-oxoindoline moieties in a more 'rigid' tricyclic system -3-[2-(3,5-diaryl-4,5-dihydropyrazol-1-yl)-4-oxo-4H-thiazol-5-iliden]-1,3-dihydroindol-2-one -allows us to achieve high cytostatic activity in 60 strains of human cancer cells without a pronounced selective effect [9,12]. All the three compounds -3288, 3833 and 3882 -are structurally similar and belong to a group of pyrazoline-thiazolidinoneisatins which were patented by us and have a noticeable antineoplastic activity in vitro that led us to study their effect on laboratory animals [12,13].…”
mentioning
confidence: 99%
“…Les-3833 was highly active towards the non-small-cell lung cancer cell line HOP-92 (GI 50 < 0.01 µM), colon cancer line HCT-116 (GI 50 = 0.018 µM), CNS cancer cell line SNB-75 (GI 50 = 0.0159 µM), ovarian cancer cell line OVCAR-3 (GI 50 = 0.0216 µM), and renal cancer cell line RXF 393 (GI 50 = 0.0197 µM) [18,21]. Les-3833 also demonstrated lower general toxicity in vivo compared with that of doxorubicin [10,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%